2012
DOI: 10.2350/11-03-0997-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of WT1 in a Human Fetus with Evolving Bronchial Atresia, Pulmonary Malformation and Renal Agenesis

Abstract: The association of peripheral bronchial atresia and congenital pulmonary airway malformation (CPAM) has recently been recognised, but the pathology of the lesions evolving together has not been described. We present autopsy findings in a 20 week fetus showing areas of peripheral bronchial destruction and airway malformation consistent with developing CPAM in the right lung supporting a causal relationship between these lesions. This fetus also had congenital heart defect, bilateral renal agenesis and syndactyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…MLPA investigations in a renal agenesis fetus with abnormal WT1 expression in liver mesothelium suggested that wt1 was not mutated in this fetus (Loo et al. 2012a ). The wt1 −/− mouse model shows reduced liver size, abnormal stellate cell development and diaphragmatic defects (Ijpenberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…MLPA investigations in a renal agenesis fetus with abnormal WT1 expression in liver mesothelium suggested that wt1 was not mutated in this fetus (Loo et al. 2012a ). The wt1 −/− mouse model shows reduced liver size, abnormal stellate cell development and diaphragmatic defects (Ijpenberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Monozygotic twins with congenital nephrotic syndrome caused by a WT1 mutation have been reported to have died due to sepsis and extensive thrombosis of central venous system and sepsis and sudden heart failure at ages 23 weeks/13.5 months, respectively [ 112 ]. WT1 misexpression has been reported in autopsy findings from two human fetuses, displaying congenital pulmonary airway malformation, bilateral renal agenesis, and congenital heart defects [ 113 ]. Shortly after, re-evaluation of autopsy data from fourteen additional fetuses with combined renal agenesis and cardiac anomalies revealed abnormalities of Wt1 expression, mostly in liver mesenchymal cells.…”
Section: Wt1 In the Adult Heart And Cardiac Pathologiesmentioning
confidence: 99%
“…Loss of WT1 results in reduced cardiomyocyte mass, pericardial hemorrhage, thinning of the myocardial wall, and embryonic lethality [49,51]. Mutations in the WT1 gene have also been associated with pulmonary dysplasia [52], hypoplastic lung malformation [53], diaphragmatic hernia [54], decreased mesothelial cell entry into the lung [18], and mesothelioma [55]. In addition, WT1 plays a crucial role in liver development.…”
Section: Signaling Pathways and Transcriptional Control Involved Imentioning
confidence: 99%